Competitive Fitness of Influenza B Viruses Possessing E119A and H274Y Neuraminidase Inhibitor Resistance-Associated Substitutions in Ferrets. - Philippe Noriel Q Pascua; Bindumadhav M Marathe; Andrew J Burnham; Peter Vogel; Richard J Webby; Robert G Webster; Elena A Govorkova (PLoS ONE, 2016)
Neuraminidase (NA) inhibitors (NAIs) are the only antiviral drugs recommended for influenza treatment and prophylaxis. Although NAI-resistant influenza B viruses that could pose a threat to public health have been reported in the field, their fitness is poorly understood. We evaluated in ferrets the pathogenicity and relative fitness of reverse genetics (rg)-generated influenza B/Yamanashi/166/1998-like viruses containing E119A or H274Y NA substitutions (N2 numbering). Ferrets inoculated with NAI-susceptible rg-wild-type (rg-WT) or NAI-resistant (rg-E119A or rg-H274Y) viruses developed mild infections. Growth of rg-E119A virus in the nasal cavities was delayed, but the high titers at 3 days post-inoculation (dpi) were comparable to those of the rg-WT and rg-H274Y viruses (3.6-4.1 log10TCID50/mL). No virus persisted beyond 5 dpi and replication did not extend to the trachea or lungs. Positive virus antigen-staining of the nasal turbinate epithelium was intermittent with the rg-WT and rg-H274Y viruses; whereas antigen-staining for the rg-E119A virus was more diffuse. Virus populations in ferrets coinoculated with NAI-susceptible and -resistant viruses (1:1 mixture) remained heterogeneous at 5 dpi but were predominantly rg-WT (>70%). Although the E119A substitution was associated with delayed replication in ferrets, the H274Y substitution did not measurably affect viral growth properties. These data suggest that rg-H274Y has undiminished fitness in single virus inoculations, but neither rg-E119A nor rg-H274Y gained a fitness advantage over rg-WT in direct competition experiments without antiviral drug pressure. Taken together, our data suggest the following order of relative fitness in a ferret animal model: rg-WT > rg-H274Y > rg-E119A.